ADAPTIVE FUZZY-SLIDING MODE CONTROLLER FOR A HELICOPTER-LIKE TWIN ROTOR MIMO SYSTEM - CHELIHI, A.; TOUBA, M. (Courrier du Savoir, 2017)
This paper addresses the attitude control problem for a twin rotor unmanned helicopter driven by DC motors. The control objective is to have the helicopter attitude, i.e., pitch and yaw angles, track specified angles. From the considered dynamics of the plant, it is observed that the main difficulty of the control problem is due to the existing nonlinear coupling effects between the two perpendicular rotors. Hence, an adaptive control approach based on the fuzzy-sliding mode controller is developed to solve the problem. In the controller design, firstly, the twin rotor multiple-input multiple-output system (TRMS) is decoupled into two single-input–single-output systems, and the cross couplings can be considered as disturbances to each other. Then, a fuzzy-sliding mode controller is designed for each of them. The stability of the overall closed-loop system is proven to be asymptotically stable based on the Lyapunov theorem. In order to demonstrate the applicability of the proposed control scheme, computer simulations is shown.